2017
DOI: 10.1002/jee.20163
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Misconceptions about Semiconductors and Use of Knowledge in Simulations

Abstract: Background Little research exists on students' misconceptions about semiconductors, why they form, and what role educational resources like simulations play in misconception formation. Research on misconceptions can help enhance student learning about semiconductors.Purpose (Hypothesis) This project sought to identify students' misconceptions about three semiconductor phenomena -diffusion, drift, and excitation -and to determine if prior knowledge, knowledge acquired from watching animated simulations, or both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 40 publications
(74 reference statements)
0
28
0
Order By: Relevance
“…We argue that attributing student learning or their misconceptions to features of a simulation tool leads educators to place too much reliance on the technology itself. Therefore, less than satisfactory learning gains naturally lead to conclusions that we need to invest in the costly development of more effective technologies (e.g., Nelson et al, ). Rather, in our study, we recognize a class environment in which an existing technology can be leveraged to become more effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that attributing student learning or their misconceptions to features of a simulation tool leads educators to place too much reliance on the technology itself. Therefore, less than satisfactory learning gains naturally lead to conclusions that we need to invest in the costly development of more effective technologies (e.g., Nelson et al, ). Rather, in our study, we recognize a class environment in which an existing technology can be leveraged to become more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we found that only a subset of students provided responses that fully aligned with the normatively correct explanations; for example, only approximately 40% correctly answered a summative question in the Thermodynamic Work IVL, where the correct answer involves mentioning net work done to the system. Similarly, Nelson et al (), who used animated simulations to demonstrate the microscopic phenomena of electrons in semiconductor materials, reported normatively correct answers for only approximately 20% of the student responses. Such results indicating student learning difficulties seem to align with the claim that misconceptions are persistent and robust (Chi, ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings of the context-dependent nature of comprehension align well with the knowledge in pieces perspective of conceptual change, which posits that students' conceptual knowledge is a collection of pieces that are cued depending on the context of the problem. While there is still considerable debate about whether conceptual knowledge is in pieces or more monolithic [2], [7], [26], [27], we based our project on the knowledge-in-pieces perspective based on its alignment with prior findings in the micro-level view of representations.…”
Section: Context-dependence Of Conceptual Understandingmentioning
confidence: 99%
“…Students were often inconsistent in how they revealed their conceptual understanding across these different modalities. While many studies in the conceptual understanding literature have studied the structure of students' conceptual knowledge, these studies focus on introductory courses on mechanics [31], astronomy [6], heat [32] and circuits [33] with only a small number of recent studies in more advanced engineering topics such as shear stress [24], [34], motion in dynamic systems [35] and drift/diffusion [27].…”
Section: Context-dependence Of Conceptual Understandingmentioning
confidence: 99%